Chromatogram and Spectram Profiles Antimalarial Isolate from Dichloromethane Extract of Artocarpus champeden Spreng. Stem Bark - Nuri Nuri (Jurnal ILMU DASAR, 2007)
The isolate which possessed antimalarial activity had been isolated from dichloromethane extract of Artocarpus champeden Spreng. Stem bark. The isolate inhibited Plasmodium falciparum growth in vitro by IC 0.024±0.011 μg/ml. Chromatogram and spectram of isolate analysis showed that it contained flavonol as a  major compound.